Law, Economics and Finance of the Real Estate Market A Perspective of Hong Kong and Singapore - Li, Rita Yi Man.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The symbiosis between the law, economics and finance is evidenced in our daily lives. This book elucidates the relationship between these factors in Singapore and Hong Kong in direct and indirect real estate market. In Singapore, for example, there is an inseparable relationship between law, economics, finance and the HDB market. The book also showcases the concept of invitation to treat and offer, monetary compensation for environmental externalities under the lens of institutional economics. It also sheds light on the relationship between financial crisis, regulations, housing prices and indirect real estate market.
Law, economics and finance issues in Singapore$1 (Bs housing development board flats -- Internalization of environmental externality in dwellings: review of court cases in Hong Kong in the past two decades -- The institutional analysis of fittings in residential units -- Asymmetric information and residential entrepreneurs$1 (Bchoice on provision of house fittings -- Property, credit and business cycles in Hong Kong -- Should we abandon the concept of artistic craftsmanship in the Copyright Act in Australia? -- An offer, an invitation to treat and transaction costs -- The effect of the global subprime financial crisis on the macroeconomy and the housing market in the UK -- Changes from the visible hand to the invisible hand: The land market in Hong Kong before and after the Asian Financial Crisis -- An overview of regulations that protect indirect real estate investors in Hong Kong during financial crises.s
Keywords: Economics; Public finance; Commercial law; Economics/Management Science; Law and Economics; Financial Law/Fiscal Law